Estudo do desempenho da transmissão subterrânea via LoRa para o monitoramento de sistemas subterrâneos visando aplicações em sistemas de distribuição de água - Villarim, Andréa Willa Rodrigues (2023)
Industry 4.0 seeks solutions in various areas, such as intelligent automation, data genera- tion/exchange and production process analysis. The adaptation of companies to the reality of this industry new generation makes it necessary to replace the equipments previously used by smart devices, using the IoT (Internet of Things) concept in low-cost equipment to monitor the state of variables of a given system. This monitoring can be performed using intelligent microsensors scattered and interconnected by wireless communication channels. An important issue to be considered when it comes to microsensors is the communication technology used, since it is the part that determines the transmission range of the data obtained and is the main responsible for system energy consumption. Some applications that need system monitoring are located in an underground environment, such as monitoring variables in a water distribution network to loss control. Considering the various challenges presented by communication in an underground environment, a study of the performance of a wireless communication technology selected to operate in such scenario is proposed. In this context, the performance of LoRa techno- logy was analyzed, as it presents characteristics of interest, such as long transmission range and low energy consumption. This thesis presents a study of LoRa communication technology perfor- mance in underground environments, with the evaluation of several communication parameters between transmitter and receiver. The analysis of the communication performance considered the influence of several variables to evaluate the applicability of this type of communication, already quite explored in conventional networks, for use in underground systems, aiming at the application in smart cities, such as for the monitoring of water distribution systems.